PERBANDINGAN MODEL CHILDREN LEARNING IN SIENCE (CLIS) DAN MODEL JIGSAW TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK KELAS V SDN UNGGULAN BONTOMANAI GOWA - Az-Zahrah, Fatimah; Saleh, Chairati; Afiif, Ahmad (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to determine the differences in scientific literacy skills of fifth-grade students of SDN Unggulan Bontomanai Gowa who are taught using the Children Learning in Science (CLIS) model and the jigsaw cooperative model. The type of research used is a quasi-experimental with a pre-test-posttest nonequivalent control group design. The study population was all 88 fifth-grade students. Through a multistage random sampling technique, 15 students were selected in experimental class 1 taught with the CILS model, and 15 students in experimental class 2 taught with the jigsaw cooperative model. To measure students' scientific literacy skills, a multiple-choice test instrument was used. The data analysis techniques used were descriptive analysis and inferential analysis. The study result showed that the average score of the scientific literacy test results of students taught using CLIS model was 76, and the average score of the scientific literacy test results of students taught using the jigsaw cooperative model was 70. The results of the two-sample t-test showed a t value = 0.026 < 0.05. This indicates that Ha is accepted, which means there is a difference in the results of the scientific literacy test between students taught using CLIS model and the jigsaw cooperative model.